2019
DOI: 10.1002/iub.2102
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA IGF2AS regulates high‐glucose induced apoptosis in human retinal pigment epithelial cells

Abstract: High‐glucose‐induced retinal tissue impairment is the major pathological phenotype of diabetic retinopathy. In an in vitro diabetic apoptosis cell model, we evaluated the function of long noncoding RNA, insulin growth factor 2 antisense (IGF2‐AS) in high‐glucose‐injured human retinal pigment epithelial cells. A human retinal pigment epithelial cell line, ARPE‐19 was incubated with high‐glucose in vitro to induce apoptosis. SiRNA‐mediated IGF2‐AS downregulation was conducted in ARPE‐19 cells to evaluate its eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Previous studies have highlighted the importance of HDAC6 inhibition in regulating oxidative stress and inflammation in a variety of diseases, especially in DR (Shi et al 2017;Yi et al 2019;Zhang et al 2019a). The effect of Cay, a novel inhibitor of HDAC6, was investigated in this research, and we demonstrated that Cay treatment It is also worth noting that robust evidence suggests that sustained hyperglycemia triggers apoptosis in RPE cells, which is a major pathological change in the eyes of patients with DR (Willermain et al 2018;Yu et al 2019;Zhang et al 2019b). Numerous studies unveil that inhibition of apoptosis of RPE cells contributes to protect against DR (Jiang et al 2017;Yu et al 2018).…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies have highlighted the importance of HDAC6 inhibition in regulating oxidative stress and inflammation in a variety of diseases, especially in DR (Shi et al 2017;Yi et al 2019;Zhang et al 2019a). The effect of Cay, a novel inhibitor of HDAC6, was investigated in this research, and we demonstrated that Cay treatment It is also worth noting that robust evidence suggests that sustained hyperglycemia triggers apoptosis in RPE cells, which is a major pathological change in the eyes of patients with DR (Willermain et al 2018;Yu et al 2019;Zhang et al 2019b). Numerous studies unveil that inhibition of apoptosis of RPE cells contributes to protect against DR (Jiang et al 2017;Yu et al 2018).…”
Section: Discussionmentioning
confidence: 66%
“…However, to date, no protein has yet been identified. There have, however, been a number of reports that IGF-IIas may function epigenetically as a lncRNA with effects on cell proliferation and invasion [61], apoptosis [62], and angiogenesis [63]. All of these reports found that these effects of IGF-IIas were reversed by increased expression of IGF-II and were consistent with an effect of IGF-IIas to suppress IGF-II expression even though no actual mechanism for this has yet been confirmed.…”
Section: Igf-ii: An Imprinted Multifunctional Metabolic Genetic Locimentioning
confidence: 99%
“…6 Recently, a novel lncRNA, IGF2 antisense RNA (IGF2-AS), was identified as a critical player in human disease. IGF2-AS was proposed to be closely associated with high-glucose-induced apoptosis in diabetic retinopathy 7 and angiogenesis in type 2 diabetes. 8 Moreover, IGF2-AS was shown to be activated by STAT3, and increased hepatitis C virus replication.…”
Section: Introductionmentioning
confidence: 99%